The unforgettable cooperation of Aimé Bonpland and Alexander von Humboldt - Frank Holl (Bonplandia, 2020)
The article analyses Aimé Bonpland’s role during the American expedition with Alexander von Humboldt (1799 to 1804). This role was more important than previously assumed, as was Bonpland’s later work in Latin America. Bonpland also conducted botanical, zoological and geological research there. Above all, he rendered outstanding services to agriculture there with new cultivation and breeding methods, especially in the cultivation of yerba mate. In his later years Bonpland initiated a project to transfer agriculturally useful plants from Argentina to the French colony of Algeria. Over 80 years old, from 1855 until his death in 1858, he worked as the first director on the establishment of a natural history museum in Corrientes. It was one of the oldest in Argentina and the first state institution in the interior of the country. Bonpland reflected on all this in a detailed correspondence with Alexander von Humboldt. The article also analyses the three contradictory reports by the German physician and travel writer Robert AvéLallemant, who visited Bonpland in Santa Ana shortly before his death. In doing so, he drew a negative image of the researcher that still influences historical record today. A correction is urgently needed.